Theory of demand--real and monetary - Morishima, Michio (Oxford : Clarendon Press, 1973)
The book contains a number of papers presented by various authors on the theory of consumer's demand and two survey articles on qualitative economics and separable utilities. It is useful to undergraduates and researchers in the field of economic theory of demand and qualitative economics.
Includes index
Bibliography: p. [316]-326.
usc 12/02/2018
Loans
Keywords: Consumption (Economics)